Development of a New Media Marketing and Planning Course Based on Project-Based Learning combined with Outcome-Based Education Concept to enhance Problem-Solving Ability in Advertising at Xi'an University - Gao , Linna; Onyon, Nitikorn; Nuansri, Mesa (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and aim: At present, the phenomenon of insufficient problem-solving ability of college students in China is more prominent. The project-based learning（PBL) combined with the outcome-based education (OBE) concept provides new ideas and methods for addressing the problem of insufficient problem-solving ability among college students. The PBL combined with OBE teaching offers effective ways and means to enhance problem-solving ability. Outcome-based education concept (OBE) emphasizes student learning outcomes and focuses on the ability and qualities students acquire during the learning process. While project-based learning (PBL) enables students to participate in solving actual projects, clarifying their learning goals and outcomes, and enhancing their learning motivation and enthusiasm. This teaching model emphasizes practical ability. It focuses on cultivating students' practical ability by having them apply learned knowledge and ability in actual projects, thus improving their problem-solving and practical operation ability, which aligns with the requirements for practical ability in the advertising field. It promotes cooperation and innovation. PBL usually requires students to complete projects in groups, helping to cultivate their cooperation ability and team spirit. At the same time, during the project implementation process, students need to continuously propose innovative solutions, which also helps cultivate their innovation consciousness and innovation ability. This study aims to develop and evaluate the effectiveness of a new media marketing and planning course based on PBL combined with OBE teaching to enhance problem-solving ability in advertising students. Materials and approaches: The study employed a three-phase research design involving phase 1 was studying the background information through reviewing documents and interviewing experts and students, phase 2 was constructing and verifying the developed course by 5 experts, and phase 3 was implementing the course with the sample of 40 junior Advertising students at Xi'an University which were derived by cluster random sampling. The research instruments used to collect data in this phase were as follows:1) scoring rubric of students' problem-solving ability with reliability of 0.84. 2) questionnaire for students' satisfaction with the reliability of 0.75. Data collection was relevant to test papers and scales, and data were analyzed by using statistics including; means, standard deviations, t-test for dependent samples, and one sample t-test. Results: After implementation of a new media marketing and planning course based on project-based learning combined with outcome-based education concept, it revealed that 1) posttest scores of students' problem-solving ability is greater than pretest at.01 levels of statistical significance (t39= 16.01, p = 0.001). 2) students' satisfaction after implementing the course was statistically greater than the criterion of 70% at a.01 level of statistical significance (t39 =19.51, p = 0.001). Conclusion: The PBL combined with OBE teaching provides effective ways and methods for improving college students' problem-solving abilities. By clarifying learning outcomes, emphasizing practical ability, and promoting cooperation and innovation, the PBL teaching methods model can better meet the requirements for problem-solving ability in modern education and the advertising field.